Beyond structural adjustment and economic recovery : development prospects and policy for Africa - Hope, Kempe Ronald (1998)
Reviews the positive economic recovery impact of structural adjustment programme (SAPs) in Africa. Analyzes development prospects and policy for the continent in the post-SPA era beyond 2000.